Analysis Of Factors Affecting Interest In Using The Epuskesmas Application As A Revenue Information System At Puskesmas Mojokerto District - Yulianti, Sri; Tikasari, Nopi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to explore the determinants that influence employees' interest in utilising the ePuskesmas application as a revenue information system within the Mojokerto District Health Centre. The application was developed to support digitisation in recording and reporting health service revenue administration. This study used quantitative methods through a survey involving 81 respondents from 27 Puskesmas, including administrative officers, cashiers, treasurers, and accountants. A total of 70 usable questionnaires were analysed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach with the help of SmartPLS software. The results of the analysis show that performance expectations, perceived ease of use, and availability of infrastructure support have a significant and positive influence on interest in using the application. In contrast, social influence factors do not have a significant impact. The R² value of 0.754 indicates that the model can explain 75.4% of the variability in usage interest. These findings highlight the importance of ease of use, operational effectiveness, and infrastructure support in strengthening the implementation of digital technology in primary healthcare facilities.